Developing a culture of safety in the Veterans Health Administration. - Weeks, Bill; Bagian, James P. (2000)
The VHA leadership has taken steps to promote a culture of safety by mak-ing public commitments to improving patient safety, allocating resources towardestablishment of special centers, enhancing employee education on patient safety, andproviding incentives to promote safety. The VHA is also establishing one mandato-ry and one voluntary adverse event reporting system; in the latter case, the reporterremains anonymous. Examples of nationally mandated initiatives are bar coding ofall medications and use of computerized medical record that includes order entry,laboratory and imaging results, and all encounter notes.